Common errors on panoramic radiograph: A time to reflect and review and not to sweep them under the carpet! - Ujwala Rohan Newadkar; Lalit Chaudhari; Yogita K Khalekar (SRM Journal of Research in Dental Sciences, 2016)
Introduction: There are a multitude of factors that may lead to a reduction of the diagnostic quality of panoramic radiographs. Errors in taking radiographs increase patient's radiation exposure, and also waste time and money. Inspecting the frequency and mechanism of producing errors will result in less retakes. Therefore, the aim of the study is to identify the most common positioning and technical errors in the panoramic radiographs taken in department of oral Medicine and Radiology of our institute. Materials and Methods: 2000 panoramic radiographs were photographed and reviewed under identical conditions, on a computer screen. Radiographs were evaluated by oral and maxillofacial radiologist, and frequency of errors was recorded. Results: Out of 2000 Panoramic radiographs there were 220 radiographs (11%) which were error free and 1780 radiographs (89%) with errors. The most common error observed in this sample was failure to place the tongue on the palate (48.7%) followed by chin tipped too low or too high (21.1%). Dark room errors accounted for 2.7% radiographs due to the processing errors resulting as dark and light radiographs as well scratches on them. The least frequent errors observed were the presence of radio-opaque artifacts caused by failure to remove metallic accessories, prostheses and the use of the lead apron during exposure and processing error (2.4%). Few radiographs had more than one error. Conclusion: Frequency of errors seen on panoramic radiographs are relatively high, thus training the operators, discussing the technical errors in case of occurrence are highly essential to maximize the quality of panoramic radiographs. Also clinicians need to be able to recognize the cause of the various film faults so that appropriate corrective action can be taken.